Effect of SGLT2 inhibitors versus DPP4 inhibitors on major adverse kidney events in diabetic people with varied kidney function decline - Cheng, Yu-Wen; Kao, Yi-Wei; Chen, Shao-Wei; Chan, Yi-Hsin; Chao, Tze-Fan (Frontiers in Endocrinology, 2026)
IntroductionThe comparative kidney-protective effects of sodium-glucose cotransporter 2 inhibitors (SGLT2is) versus dipeptidyl peptidase-4 inhibitors (DPP4is) in people with type 2 diabetes (T2D) with varying past estimated glomerular filtration rate (eGFR) decline rates remain unclear.MethodsThis retrospective study analyzed 4,011 propensity score-matched T2D people from a multi-center database, each with at least 2 years of eGFR data before therapy and 1 year of follow-up. The patients received either SGLT2i or DPP4i between June 2016 and December 2021.ResultsAmong paired patients, 23.7% (SGLT2i) and 25.4% (DPP4i) were rapid decliners (≥5 mL/min/1.73 m²/year). SGLT2i treatment was consistently associated with a slower eGFR decline than DPP4i, regardless of past eGFR slope. Post-treatment rapid eGFR decline decreased in both groups but remained higher in DPP4i users (20.5% vs. 15.4%). Those patients with past rapid eGFR decline receiving DPP4i rather than receiving SGLT2i remained at a higher risk for major adverse kidney events (MAKE) (a sustained 50% reduction in follow-up eGFR or the development of ESKD) and post-treatment rapid eGFR decline. Compared to DPP4i, SGLT2i therapy overall was associated with lower risks of MAKE (HR: 0.77; [95% CI: 0.64–0.94]), abrupt kidney function decline (HR: 0.76; [95% CI: 0.60–0.97]), and persistent rapid eGFR decline (HR: 0.76; [95% CI: 0.68–0.84]), with treatment benefits across different past eGFR decline categories. No difference in urinary albumin-to-creatinine ratio deterioration was observed between groups. The treatment benefits of SGLT2i over DPP4i were consistent across varying past eGFR slopes examined as a continuous variable.ConclusionsSGLT2i therapy was associated with better kidney outcomes and slower eGFR decline than DPP4i regardless of prior rapid eGFR decline.